Theory and method in higher education research. II - Huisman, Jeroen; Tight, Malcolm (Bingley, U.K. : Emerald, 2014)
Higher education research is a developing field internationally, attracting more and more researchers from a great variety of disciplinary backgrounds within and beyond higher education institutions. As such, it is an arena within which a wide range of theories, methods and methodologies are being applied. As an expanding multidisciplinary area of interest, we may also expect increased development of theory and method.This is the second volume in this series dedicated to Theory and Method in Higher Education Research. Publishing contemporary contributions to international debates regarding the application and development of theory and methodology in researching higher education, this volume aims to offer a channel for discussion, critique and innovation. It should become essential reading for the growing numbers of researchers engaging with higher education across the globe.
Theorising teaching and learning in higher education research / Peter Kandlbinder -- Finding meaning in higher education : a social hermeneutics approach to higher education research / Manfred Lueger, Oliver Vettori -- Narratives and accounts : their collection and analysis / Sara Delamont, Paul Atkinson -- Methodological meditations on producing rich narrative data / Cecilia Jacobs -- More-than-human theorising inclusive / Paul Hodge, Sarah Wright, Fee Mozeley -- Researching academic writing : what textography affords / Sue Starfield, Brian Paltridge, Louise Ravelli -- Learning architectures and communities of practice in higher education / Jonathan Tummons -- A temporal approach to higher education research / Oili-Helena Ylijoki -- Using crisp and fuzzy set-theoretic analyses for middle-range theorising : a configurational comparative approach to case-based research / Farshid Shams -- Analytic autoethnography : one story of the method / John Struthers -- The dilemma of methodological idolatry in higher education research : the case of phenomenography / Fiona Hallett -- The potential of combining phenomenography, variation theory and threshold concepts to inform curriculum design in higher education / Gerlese ôkerlind, Jo McKenzie, Mandy Lupton -- Theory development and application in higher education research : the case of threshold concepts / Malcolm Tight.
Print version record
Keywords: Education -- Higher; Education -- Research; Education -- General; "Higher & further education, tertiary education".; Philosophy & theory of education; Education; Education, Higher -- Research; Education, Higher -- Research -- Methodology